Carboplatin and Paclitaxel in Metastatic or Recurrent Cervical Cancer. Issue 4 (1st April 2009) - Pectasides, Dimitrios; Fountzilas, George; Papaxoinis, George; Pectasides, Eirini; Xiros, Nicolaos; Sykiotis, Constantinos; Koumarianou, Anna; Psyrri, Amanda; Panayiotides, John; Economopoulos, Theofanis
Abstract : Objectives: The purpose of this study was to evaluate the activity and toxicity of carboplatin and paclitaxel combination in advanced or recurrent carcinoma of the cervix. Methods: Fifty-one eligible patients with measurable advanced or recurrent cervical carcinoma were treated with carboplatin (area under the curve, 5) and paclitaxel 175 mg/m 2 every 3 weeks for 6 to 9 cycles or until disease progression or unacceptable toxicity. Results: Eight complete (16%) and 19 partial responses (37%) occurred, for an overall response rate (RR) of 53% (95% confidence interval [CI], 39%-67%). The median progression-free survival was 6 months (95% CI, 5.4-6.5 months), and the median overall survival was 13 months (95% CI, 11.4-14.5 months). The RR was higher in patients with disease outside a previously irradiated site compared with those with disease in a previously irradiated field (68% vs 30%) ( P = 0.011). Patients previously treated with chemoradiation had an RR of 28%, whereas in those previously treated with radiotherapy alone, the RR was 68% ( P = 0.023). There was no statistically significant difference between histology and response to therapy. Patients with performance status of 0 or 1 had a higher RR than those with worse performance status. Toxicity was generally mild except for myelotoxicity. Neutropenia grade 3/4 was recorded in 44% of patients, and 6% experienced febrile neutropenia. Twenty-two percent of patients experienced anemia grade 3-4, whereas 14% had thrombocytopenia grade 3-4. Three patients (6%) developed grade 3 sensory neuropathy. Conclusion: The combination of carboplatin and paclitaxel seems to have activity in advanced or recurrent cervical carcinoma with an acceptable toxicity profile.